2007
DOI: 10.1007/s00122-007-0637-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene expression between upland and lowland rice cultivars under water stress using cDNA microarray

Abstract: To elucidate the differences in the regulation of water stress tolerance between two genotypes of rice, upland-rice (UR, resistant to water stress) and lowland-rice (LR, susceptible to water stress), we constructed subtracted cDNA libraries from polyethyleneglycol (PEG)-treated and non-treated rice seedlings (IRAT109, an upland-rice variety) by suppression subtractive hybridization (SSH), from which about 2,000 recombinant colonies were picked and amplified. Then, a cDNA microarray containing these expressed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 95 publications
0
55
0
Order By: Relevance
“…Previous research showed more drought-resistance of three UR varieties we used than that of three LR varieties. Among three UR varieties drought-resistance of Haogelao and IRAT109 is more than that of Handao297 [25,30,38] .…”
mentioning
confidence: 99%
“…Previous research showed more drought-resistance of three UR varieties we used than that of three LR varieties. Among three UR varieties drought-resistance of Haogelao and IRAT109 is more than that of Handao297 [25,30,38] .…”
mentioning
confidence: 99%
“…Later Gorantla et al (2005) used functional genomics and generated a large number of ESTs from cDNA libraries and identified 589 genes involved in drought stress. Wang et al (2007) compared gene expression between upland and lowland rice cultivars under drought stress using cDNA microarray. Compared with rice, the genomes of other cereals are large and complex (Paterson, 2006).…”
Section: Use Of "Omics" Technologies For Drought Tolerancementioning
confidence: 99%
“…To survive flooding stress, plants have evolved a number of physiological and biochemical responses (Perata and Alpi 1993). It has been reported that stress tolerance is the result of a complex cascade of molecular events that include gene activation and/or upregulation of stress-induced genes contributing to stress tolerance (Wang et al 2007;Zheng et al 2004;Chaves et al 2003). Therefore, it is important to investigate gene expression patterns in eggplant roots to identify genes encoding proteins with regulatory functions or metabolism in response to flooding conditions.…”
Section: Introductionmentioning
confidence: 99%